Validating an Observation Protocol to Measure Special Education Teacher Effectiveness - Johnson, Evelyn S.; Semmelroth, Carrie L. (Journal of the American Academy of Special Education Professionals, 2015)
This study used Kane’s (2013) Interpretation/Use Argument (IUA) to measure validity on the Recognizing Effective Special Education Teachers (RESET) observation tool. The RESET observation tool is designed to evaluate special education teacher effectiveness using evidence-based instructional practices as the basis for evaluation. In alignment with other studies (Bell et al., 2012), we applied and interpreted Kane’s (2006) four inferences for trait observation: scoring, generalization, extrapolation, and decision rules. Results from this study show that acceptable levels of validity are promising for the RESET observation tool. Because the RESET observation tool is premised on the idea that by increasing the use of evidence-based practices, student achievement will also increase, further investigations into the relationship between fidelity of implementation of instruction and student achievement will be critical for moving project work forward.